Stakeholder workshop on the dissemination of findings of interventions to improve food safety in red meat vendor shops in Addis Ababa, Ethiopia - Amenu, Kebede; Dinede, Getachew; Keba, Abdi; Lam, Steven; Mekonnen, A.; Abate, Gashaw T.; Hoffmann, Vivian; Grace, Delia; Hung Nguyen-Viet (International Livestock Research Institute, 2024)
The objectives of the workshop were to share the preliminary results of CGIAR initiatives related to food safety activities in Ethiopia and discuss challenges, successes, lessons learned and the way forward.